GC-MS/MS ANALYSIS OF BROWN RICE - Krishnaveni, Marimuthu (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was undertaken to study the phytoconstituents quantitatively through gas chromatography-mass spectrometry (MS)/MS, as well as its antibacterial, antifungal activities. Methods: The ethanol extract of brown rice was used for the study. 25gram of brown rice powder was used for the extraction process. Results: Each peak in the chromatogram represents the signal created by a compound that elutes from the GC column into the detector. The size of the peaks is proportional to the quantity of the equivalent substances in the specimen analyzed. The results obtained shows the highest peak for 6-(1-hydroxymethylvinyl)-4, 8a-dimethyl-3, 5, 6, 7, 8, 8a-hexahydro-1H-naphthalen-2one, 26-Nor-5-cholesten-3Î²-ol-25-one, Propane, 1,1-diethoxy-, and stigmastan-3,5-diene. The remaining seven compounds (Stigmasteryl tosylate, Tetradecanedioic acid, 2H-1-Benzopyran-2-one, 6-acetyl-7-(acetyloxy)-4-methyl-, 3-Isopropoxy-1,1,1,7,7,7-hexamethyl,-3,5,5tris (trimethylsiloxy) tetrasiloxane, Dodecanoic acid, ethyl ester, t-Butyl hydrogen phthalate) showed moderate levels of a peak area percent except 3, 4-Dihydroxy-Î±-(isopropylaminomethyl)-benzyl alcohol (isoproterenol) as it shows only 1.73 as peak area percent, which was found to be low compared to other compounds identified. No compound was present in trace amount. The range of retention time falls within the range of 4.79 to 35.15. Conclusion: The antimicrobial property could be attributed due to the phytochemicals present in brown rice. Essential oil, sterols and various other bioactive constituents present in it would have been responsible for the antibacterial, antifungal activity. Brown rice is a whole grain which could be germinated to improve its overall health benefits. Brown rice extract finds applications in pharmaceutical preparations. Keywords: Antibacterial, Antifungal, Brown rice, Gas chromatography-mass spectrometry/mass spectrometry.